2005
DOI: 10.1121/1.1857525
|View full text |Cite
|
Sign up to set email alerts
|

Lamb mode conversion at edges. A hybrid boundary element–finite-element solution

Abstract: Two general and flexible numerical techniques based on the finite-element and boundary element methods developed by the authors in a previous paper are applied to study Lamb wave propagation in multilayered plates and Lamb mode conversion at free edges for frequencies beyond the first cutoff frequency. Both techniques are supported by a meshing criterion which guarantees the accuracy of the results when a condition is fulfilled. A finite-element formulation is directly applicable to study Lamb wave propagation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…It can be concluded that a rough criterion of k s /h = 25 is thus quite acceptable, which may be not the case for k s /h = 10. Note that it coincides well with the criterion proposed for SAFE methods by Galan and Abascal [33,34] when using 3-node triangles.…”
Section: Convergence and Accuracysupporting
confidence: 65%
“…It can be concluded that a rough criterion of k s /h = 25 is thus quite acceptable, which may be not the case for k s /h = 10. Note that it coincides well with the criterion proposed for SAFE methods by Galan and Abascal [33,34] when using 3-node triangles.…”
Section: Convergence and Accuracysupporting
confidence: 65%
“…The solution of the hybrid system directly yields the coefficients of scattered modes. In the literature, hybrid methods have already been proposed for elastic guided waves in two-dimensional straight waveguides (plates [32][33][34][35][36][37] and cylinders 38 ) as well as acoustic waves in ducts 39,40 for instance. A close relationship between hybrid and Dirichletto-Neumann approaches can be demonstrated, as done in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…They used it to develop a mode decomposition technique for an elastodynamic field and semianalytically obtained the reflection coefficients for the oblique incidence problem. In addition, it is important to understand the interaction of Lamb modes with a plate edge which has been studied and reported quite extensively [9][10][11][12][13][14][15]. It has been shown that the incident wave, interacting with a free plate edge, gives rise to a system of reflected waves, consisting of propagating and non-propagating modes.…”
Section: Introductionmentioning
confidence: 99%